1997
DOI: 10.1182/blood.v90.2.795.795_795_802
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Stimulator of Granulocyte Colony-Stimulating Factor Accelerates Recovery From Cyclophosphamide-Induced Neutropenia in the Mouse

Abstract: We have identified a small molecular weight compound, SCH 14988, which specifically stimulates in vitro granulocyte-colony stimulating factor (G-CSF ) production from activated human peripheral blood mononuclear cells and monocytes but not other cytokines or CSFs with hematoregulatory activity. In vivo administration of SCH 14988 to mice rendered neutropenic by cyclophosphamide treatment resulted in the accelerated recovery of the peripheral neutrophil compartment. This activity correlated with increased in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Because of this, efforts have been made to identify small molecular weight compounds that can be delivered at low cost as an effective therapy. A small synthetic compound, SCH 14988 (a pyridinyl-naphthyridinyl-sulfonyl acetamide), has been shown to specifically stimulate G-CSF production in vitro and in vivo [ 21 ]. In addition, Aoki et al [ 22 ] identified a stimulatory monoclonal antibody (mAb 3-4H7) from autoimmune mice that selectively stimulates G-CSF gene expression in mouse macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, efforts have been made to identify small molecular weight compounds that can be delivered at low cost as an effective therapy. A small synthetic compound, SCH 14988 (a pyridinyl-naphthyridinyl-sulfonyl acetamide), has been shown to specifically stimulate G-CSF production in vitro and in vivo [ 21 ]. In addition, Aoki et al [ 22 ] identified a stimulatory monoclonal antibody (mAb 3-4H7) from autoimmune mice that selectively stimulates G-CSF gene expression in mouse macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Aoki et al [ 22 ] identified a stimulatory monoclonal antibody (mAb 3-4H7) from autoimmune mice that selectively stimulates G-CSF gene expression in mouse macrophages. The mechanism(s) by which SCH 14988 and mAb 3-4H7 stimulate G-CSF production is unclear, but post-transcriptional regulation has been suggested in the case of SCH 14988-stimulated G-CSF production [ 21 ]. Our study demonstrated that a small molecular weight compound, SB203580, can increase the G-CSF mRNA levels through a post-transcriptional mechanism by increasing the stability of mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several protective agents have been used to reduce the toxic side effects of chemotherapy. These include administration of certain herbal remedies [Matsumoto et al, 1995;Kaneko et al, 1999;Latha and Panikkar, 1999] and chemoprotective agents [Moore and Warren, 1987;Futami et al, 1990;Chudgar et al, 1995;Fine et al, 1997;Misaki et al, 1998], which induce hematopoiesis resulting in accelerated recovery from myelosuppression and leukopenia caused by cancer chemotherapy. It is believed that these protective agents stimulate production of cytokines involved in proliferation, differentiation, and maturation of bone marrow cells.…”
Section: Introductionmentioning
confidence: 99%